EVALUATION OF NEONATAL OUTCOME BY MEASURING UMBILICAL ARTERY BLOOD PH VALUE - Frenk Krištofelc (Zdravniški Vestnik, 2002)
Background. The evaluation of neonatal outcome after delivery is being performed since 1953 by Apgar score. Since some parts of this scoring system subject to personal judgment of the evaluator, the researchers attempts are to introduce more objective method of determining neonatal outcome after delivery. Determining umbilical artery pH value is one of such attempts. Methods. We established umbilical artery blood pH value in 146 newborns after cuting umbilical cord following delivery. The same newborns were evaluated by Apgar score. By analysis of the variance both evaluating methods of neonatal outcome were compared regarding their ability to predict neonatal indisposition for duration of hospitalization. Neonatal morbidity and neonatal hospitalization duration were the criteria for neonatal indisposition. Results. Apgar score value following 5th minute after delivery is importantly linked with neonatal morbidity and neonatal hospitalization duration. Conclusion. Umbilical artery blood pH value can’t be used as a substitute to Apgar score. Apgar score after 5th minute is the sole predictor of neonatal outcome.